Retrospective of barley breeding in the FSBSI “ARC “Donskoy” - E. G. Filippov; A. A. Dontsova; D. P. Dontsov (Зерновое хозяйство России)
The current paper has presented a historical excursion and an overview of scientific research on breeding and seed production of winter and spring barley in the Federal State Budgetary Scientific Institution Agricultural Research Center “Donskoy”. The Southern Federal District includes 8 subjects of the Russian Federation, namely Sevastopol; republics of Adygea, Kalmykia, Crimea; Krasnodar Territory, Astrakhan, Volgograd and Rostov regions. Barley is the main grain forage crop in terms of sown area. Don farmers have long shown interest in this valuable, diverse crop, very unpretentious to the cultivation conditions. Barley breeding work began in our institution in 1932 and is still ongoing, with short interruptions, to the present. Research was carried out in various areas: breeding of winter, spring and facultative barley, seed production and technology of their cultivation. In the XXI-st century, the researchers of the barley department developed new innovative directions in barley breeding, there were developed two-row brewing varieties with high malting rates (the variety ‘Randevu’) in winter barley breeding and in spring barley breeding there were developed fodder barley (green fodder) varieties (the variety ‘Novik’), which were previously absent in the State List of the Russian Federation. In 2014 there were opened new directions in the department, namely the development of hulles spring barley varieties and awnless winter barley varieties. Since 2016, there has been carried out an active work to identify winter barley lines that are genetically resistant to net blotch. Together with the All-Russian Research Institute of Radiology and Agroecology, there was carried out an estimation of the radiosensitivity of winter and spring barley varieties to identify varieties being resistant to the environmental stress factors. Based on research materials, there were successfully defended 11 candidate and two doctoral dissertations, there were published eight monographs and more than 400 scientific articles.